An efficient approach to the preparation of polyethylene magnetic nanocomposites. (5th August 2016) - Nisar, Muhammad; Bergmann, Carlos; Geshev, Julian; Quijada, Raúl; Galland, Griselda Barrera
Abstract: In the present work, a new method is developed for the preparation of polyethylene magnetic nanocomposites by in situ polymerization. Carbon nanotubes (CNTs), synthesized by the chemical vapor deposition method using ferrocene as the precursor and catalyst and silica (SiO2 ) as the support, were used as fillers and compared with a commercial CNT. The synthesized nanofillers had iron magnetic particles encapsulated in CNTs. The fillers were well dispersed into the polyethylene matrix, as evidenced by scanning electron microscopy (SEM) and transmission electron microscopy (TEM) micrographs. Even for a very low filler concentration of 0.9 wt%, the presence of magnetic nanoparticles changed the diamagnetic nature of the polymer matrix to a ferromagnetic one. The thermal properties showed that the polymeric matrix did not change their properties significantly. Graphical abstract: Highlights: A new magnetic nanocomposite based in polyethylene was obtained. Extremely high coercivity values (∼1000 Oe) were achieved. Encapsulation of Fe in CNTs protected the iron NPs from oxidation and aggregation. I n situ polymerization avoids dipolar interactions that destabilize the magnetized state.